Nanosonosensitizers With Ultrasound-Induced Reactive Oxygen Species Generation for Cancer Sonodynamic Immunotherapy - Cheng, Danling; Wang, Xiaoying; Zhou, Xiaojun; Li, Jingchao (Frontiers in Bioengineering and Biotechnology, 2021)
Immunotherapy is a promising therapeutic strategy for cancer, while immunotherapy has been demonstrated to encounter the issues of low immune responses and underlying immune-related adverse events. Sonodynamic therapy (SDT) that utilizes sonosensitizers to produce reactive oxygen species (ROS) triggered by ultrasound (US) stimulation can be used to ablate tumors, which also leads to induction of immunogenic cell death (ICD), thus achieving SDT-induced immunotherapy. Further combination of SDT with immunotherapy is able to afford enhanced antitumor immunity for tumor regression. In this mini review, we summarize the recent development of nanosonosensitizers with US-induced ROS generation for cancer SDT-immunotherapy. The uses of nanosonosensitizers to achieve SDT-induced immunotherapy, combinational therapy of SDT with immunotherapy, and combinational therapy of SDT with multiple immunotherapies are briefly introduced. Furthermore, the current concerns and perspectives for the development and further clinical applications of these nanosonosensitizers for SDT-combined immunotherapy of cancer are discussed.